Dosimetry of indigenously developed (192)Ir high-dose rate brachytherapy source: An EGSnrc Monte Carlo study - Sahoo, Sridhar (J Med Phys, 2016)
Clinical application using high-dose rate (HDR) (192)Ir sources in remote afterloading technique is a well-established treatment method. In this direction, Board of Radiation and Isotope Technology (BRIT) and Bhabha Atomic Research Centre, India, jointly indigenously developed a remote afterloading machine and (192)Ir HDR source. The two-dimensional (2D) dose distribution and dosimetric parameters of the BRIT (192)Ir HDR source are generated using EGSnrc Monte Carlo code system in a 40 cm dia × 40 cm height cylindrical water phantom. The values of air-kerma strength and dose rate constant for BRIT (192)Ir HDR source are 9.894 × 10(−8) ± 0.06% UBq(−1) and 1.112 ± 0.11% cGyh(−1)U(−1), respectively. The values of radial dose function (g(L)(r)) of this source compare well with the corresponding values of BEBIG, Flexisource, and GammaMed 12i source models. This is because of identical active lengths of the sources (3.5 mm) and the comparable phantom dimensions. A comparison of g(L)(r) values of BRIT source with microSelectron-v1 show differences about 2% at r = 6 cm and up to 13% at r = 12 cm, which is due to differences in phantom dimensions involved in the calculations. The anisotropy function of BRIT (192)Ir HDR source is comparable with the corresponding values of microSelectron-v1 (classic) HDR source.